Development and validation of an educational pamphlet: technology for home care of pressure injuries: PARA EL CUIDADO DOMICILIARIO DE LAS LESIONES POR PRESIÓN (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To create and validate an educational pamphlet focused on home care for pressure injuries. Method: This methodological study was conducted in three stages: topic development, pamphlet creation, and content validation by experts. The pamphlet was designed using the Canva® digital graphic design platform, considering a dynamic, self-explanatory approach suitable for the target audience, featuring a light and attractive appearance with simple language. For content validation, the Content Validity Index (CVI) was used. Results: The pamphlet, titled “Pressure Injuries and Home Care: Let’s Talk About It?”, was validated by eight experts with an overall CVI above ≥ 0.78. Due to concerns raised by the experts regarding linguistic accessibility, a content review and textual adjustments were made for the final version. Conclusion: The constructed, validated pamphlet has demonstrated potential for use and improvement in home care for people with pressure injuries. Future research should focus on validating the usability of the technology by users.